Older Adults Recently Diagnosed with Age-Related Vision Loss: Readjusting to Everyday Life. Issue 4 (1st October 2016) - Magnus, Eva; Vik, Kjersti
Abstract : This study aims to explore how older adults recently diagnosed with age-related vision loss experience and readjust to their new everyday lives. Ten individuals participated in qualitative interviews. Using a grounded theory analyzing strategy, the core category identified was named "Good days—an everyday life with small and wide-ranging adjustments, " including three categories: (1) Not as usual or as planned; (2) Holding on to important activities; and (3) Holding on to independence. Although participants navigated new challenges, they also expressed a fear of more extensive vision loss that would threaten additional losses of activity and independence. The article concludes with recommendations for practice.